203 PD-L1 Expression in Primary Effusion Lymphoma With Clinical Correlation. (11th January 2018) - Coberly, Jared; Gupta, Arjun; Naina, Harris; John, George; Chen, Weina
Abstract: Background: Programmed cell death ligand 1 (PD-L1) is a cell surface glycoprotein that down-regulates the immune responses through binding to its inhibitory receptor (PD-1) on T cells. Primary effusion lymphoma (PEL) is an uncommon, large B-cell non-Hodgkin lymphoma associated with immunosuppression. Given the lack of literature on PD-L1 expression in PEL and potential targetable immunotherapy, we evaluated PD-L1 expression in PEL with clinical correlation. Design: Seven cases of PEL with both tissue and clinical data were available for review. IHC was performed using monoclonal antibodies against PD-L1 (SP142) and PD1 (NAT105). PD-L1 immunoreactivity was scored in the neoplastic cells (nPD-L1) as percentage (%) of neoplastic cells and was stratified into low (< 5%) and high expression (≥5%) groups. We also scored PD-L1 expression in the stromal cells (sPD-L1) as the percentage of cells staining in tumor region. PD-1 was scored as the number of positive T-cells per high power field (HPF). Results: All subjects were men. The median age was 64 years. Specimen types included five pleural or pericardial fluids, and two extracavitary lymph nodes. A higher expression of nPD-L1 was observed only in two cases, both extracavitary lesions. nPD-L1 positivity showed no significant relationship in regard to age, HIV or EBER status, PD-1 on T cells, or stromal/macrophage PD-L1 percentage (range 2%40%, median 5%). Over a median follow-up of 1.8 months (range 0.53–80.10 months), all two patients with a higher nPD-L1 expression died, whereas three of five patients died in the low nPD-L1 group ( P > .05). Conclusion: This is the first report to describe PD-L1 expression in both neoplastic cells and tumor infiltrating stroma/macrophages in PEL with clinicopathologic correlation. Our observations suggest that induction of local immunosuppression by the PD-1/PD-L1 pathway may differ between cavitary and extracavitary disease. Further studies are needed to validate these results.